OPEN SELECTION MANAGEMENT OF STATE CIVIL APPARATUSIN THE MINISTRY OF ADMINISTRATIVE REFORM AND BUREAUCRACY REFORM - Amalia, Rizki (Sosiohumaniora, 2020)
Based on the mandate of the State Civil Apparatus Law number 5 of 2014, one of the policies for filling up the State Civil ApparatusHigh Leadership Position is through open selection. The implementation of State Civil Apparatus’s open selection in 2016 at the Ministry of Administrative and Bureucratic Reform experienced twice the extension of open selection registration. There was a decrease in participants in the open selection in 2016 compared to the previous year. The results of the paper selection and interview selection have not been supplemented by the participants’ selection scores on each announcement letter issued by the Ministry of Administrative and Bureucratic Reform. This study aims to determine and analyze the management of the open selection of the state civil apparatus in the Ministry of Administrative Reform and Bureaucratic Reform. This type of research is descriptive research with a qualitative approach. In this research, the analysis of the management of open selection State Civil Apparatuswas conducted with the aspects studied were planning, organizing, actuating and controlling. The results showed that the management of State Civil Apparatus’s open selection of the state civil apparatus in The Ministry of Administrative and Bureaucratic Reform already performing quite well in the aspects of organizing and controlling, but in the aspects of planning and actuatingstill encountered obstacles.